Academic Hardiness and Healthy Lifestyle Behavior on Student Athletes - Wijaya, Michael; Huwae, Arthur (Universitas Negeri Semarang, 2024)
This study aims to determine the relationship between academic hardiness and healthy lifestyle behavior in student athletes. The method used is quantitative with a correlational design. The data analysis method employed the Karl Pearson product-moment correlation test. The population in this study were all student athletes, in this case including high school students and university students in Indonesia. A total of 174 student athletes participated in the study using snowball sampling technique. The research measurements used the Revised Academic Hardiness Scale (α = 0.898) and The Health-Promoting Lifestyle Profile II (α = 0.885). The results showed a significant positive relationship between academic hardiness and healthy lifestyle behavior (r = 0.161 and sig. = 0.017). This indicates that academic hardiness is one of the factors associated with the improvement of healthy lifestyle behavior in student athletes. The implications of this research suggest that future researchers should focus on studying student athletes who reside in athletic dormitories or attend schools or universities with a sports-based curriculum and are also recipients of sports scholarships.